Frequency of consumption of selected foods by people with acne vulgaris - Anna Żygało; Beata Całyniuk (National Institute of Public Health - National Institute of Hygiene, 2024)
Background Acne is an inflammatory disease affecting adolescents during puberty, but also adults. Determinants of acne may include genetic predisposition as well as diet. The Western diet is rich in processed products with low nutrient density, resulting in a lack of supply of many essential minerals that are needed for the body to function properly. Objective The aim of this study was to assess the dietary behaviour of people with acne vulgaris and respondents' selfassessment of the severity of acne lesions after consumption of selected products. Material and Methods The study was carried out by means of an online, self-administered questionnaire, a link to which was inserted in group of people struggling with acne on a social network. Results More than half of the respondents said that acne was present in their parents. Almost 91% of the women surveyed said that acne lesions were exacerbated before menstruation. Respondents were most often treated by a dermatologist. The most common foods consumed by the respondents were milk and milk products and wheat bread. The least frequently consumed products were: sultanas, cornflakes, alcohol and fizzy drinks. Statistical analysis showed a strong strength of association between consumption of white rice, fast food, omega-6-rich oils on the severity of acne lesions, while sultana consumption was very strong correlated. In addition, the study showed an almost certain correlation regarding the consumption of white flour pasta on acne lesions. Conclusions Statistical analysis showed a relationship between the consumption of white rice, white flour pasta, fast food products, sultanas, oils rich in omega-6 fats and the exacerbation of acne lesions.